(3jfGHjY GdYdhes - (3GdNhjj , CMeO Hf Ndjd Hf SYGOI Hf LYaQ Hf YjSi GdegdHj GdNhjj, TeS GdOjf CHh GdYHGS,J (B637 (3g` s ((3eGehf Hf eMeO Hf eCehf GdETWgGfi s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCTjGA hHYO aEfi COGA hSeY GdOYGA hCLeY ajg afhf SHYI aGdJaSjQ hGdMOjK hGdabg s
(3BNQgG (B:s
(3GdeSJedMI GdSGHYI ai af GdESWQdGH hBNQ eG ajg hdYd Gddg jQMe Pdi hbUhQi s
(3YdjgG Jedc hbQGAIs
(3bSeg Edi SHYI afhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B121 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B216s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdeYGQa GdYGeIs